Integration of Marine and Land-based Spatial Planning: A Systematic Review of Global Trends, Challenges, and Best Practices for the Indonesian Context - Radiwan Helmi; Kiky Permana Setiawan (Journal of Geoscience, Engineering, Environment, and Technology, 2025)
Integrating marine and land-based spatial planning is a strategic priority for Indonesia, the world's largest archipelagic country. Yet, its implementation is hampered by institutional challenges such as sectoral egos and overlapping jurisdictions. This study aims to bridge the gap between conceptualization and practical implementation by conducting a systematic literature review of 22 relevant global studies from the Scopus database up to August 3, 2025. Bibliometric analysis confirms a significant gap between the conceptual understanding of "land-sea interaction" and the operational application of "land-sea coordination". A geographical analysis reveals the dominance of research from China (59%) and a starkly minimal representation from Indonesia, indicating a critical research gap. Although various successful governance models have been identified—from centralized frameworks in China to participatory approaches in the UK—this study concludes that no single solution is universally applicable. Therefore, this study recommends an urgent research agenda focused on the Indonesian context, specifically to evaluate the synchronization of policies post-Job Creation Law, overcome institutional barriers, and develop participatory planning models capable of addressing Indonesia's unique socio-ecological complexities to sustainably realize its maritime potential.